2019
DOI: 10.33019/ijbe.v3i3.188
|View full text |Cite
|
Sign up to set email alerts
|

Employees Perception of Human Capital Practices, Employee's Productivity, and Company Performance

Abstract: This study aims to find out whether there is an influence between human capital practices and productivity on company performance. The theoretical approach raised in this study is about human capital, productivity, and company performance. The research method approach carried out in this study is quantitative, namely by regression testing, and previously testing the quality of the instrument through validity and reliability tests. The results obtained are that the practice of human capital and productivity doe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…The fit indices of the measurement models are summarized in Table (3). The results of confirmatory factor analysis showed that the measurement models have a good fit because the value of χ2 / df (chi-square divided by the degree of freedom) is less than 3, and the value of RMSEA is less than 0.08, the values of GFI, AGFI and NFI are greater than /9.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fit indices of the measurement models are summarized in Table (3). The results of confirmatory factor analysis showed that the measurement models have a good fit because the value of χ2 / df (chi-square divided by the degree of freedom) is less than 3, and the value of RMSEA is less than 0.08, the values of GFI, AGFI and NFI are greater than /9.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, only by improving human resources can we expect the desired performance of the organization and thus productivity (1,2). Studies show that under the same conditions, the only 49 Available at: www.ijethics.com reason for organizational failure that causes the organization to fail to achieve its goals is the lack of productivity of human resources (3). Employee productivity is one of the benefits of organizational excellence.…”
Section: Introductionmentioning
confidence: 99%
“…The survey method with path analysis technique is used to analyze the pattern of relationship between variables with the aim of knowing the direct and indirect effect of a set of independent variables (exogenous) on the dependent variable (endogenous). [6] The population in this study were all employees of Raharja College, Cikokol, Tangerang with a sample of 30 employees who were taken randomly. Data analysis using smart PLS 3.0 version software.…”
Section: Figure 1 Theoretical Model Of Relationship Between Research ...mentioning
confidence: 99%
“…The focus of human capital management is the management of people within an organization as a resource (Ward, 2009;Thuda & Maharani, 2019). Features of human capital management focus on optimizing the workforce.…”
Section: Human Capital Management and Employee Performance Managementmentioning
confidence: 99%
“…From an economic perspective, the management of human capital is a critical concern as it relates to overall business performance (Samson & Bhanugopan, 2022;Thuda & Maharani, 2019). Employees are arguably the most valued resource in business, while also being the most volatile (Hall, 2008;Mehale et al, 2021).…”
Section: Introductionmentioning
confidence: 99%